2007
DOI: 10.1007/s10633-007-9059-8
|View full text |Cite
|
Sign up to set email alerts
|

The mouse pattern electroretinogram

Abstract: Mouse models of optic nerve disease such as glaucoma, optic neuritis, ischemic optic neuropathy, and mitochondrial optic neuropathy are being developed at increasing rate to investigate specific pathophysiological mechanisms and the effect of neuroprotective treatments. The use of these models may be greatly enhanced by the availability of non-invasive methods able to monitor retinal ganglion cell (RGC) function longitudinally such as the Pattern Electroretinogram (PERG). While the use of the PERG as a tool to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 61 publications
4
91
0
Order By: Relevance
“…Porciatti et al searched in rats and found that pERG responses developed in parallel with pVEP results in postnatal period [31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porciatti et al searched in rats and found that pERG responses developed in parallel with pVEP results in postnatal period [31][32].…”
Section: Discussionmentioning
confidence: 99%
“…[21] On the other hand Guttob and his friends [29] and Hess et al [30] stated that PERG is normal in any type of amblyopia. This study was undertaken to investigate the effect of amblyopia on both the retinal and cortical pattern responses [31].…”
Section: Discussionmentioning
confidence: 99%
“…Pattern electroretinography was measured as previously reported (22,23,89). Mice from our colony were shipped in a "masked" fashion to the University of Miami, Miami, Florida, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial mCherry fluorescence was visualized using a Heidelberg laser-scanning ophthalmoscope outfitted with special filters for red or green fluorescence. PERGs were performed according to previous reports (49). Averaged PERGs were automatically analyzed to evaluate the major positive and negative waves with Sigma Plot (Systat Software Inc.).…”
Section: Methodsmentioning
confidence: 99%